Wpływ traktatu lizbońskiego na regulacje imigracyjne UE ze szczególnym uwzględnieniem zasady solidarności i sprawiedliwego podziału odpowiedzialności między państwami członkowskimi - Krzysztof Załucki (Ksiegarnia Akademicka Publishing, 2019)
The Influence of the Treaty of Lisbon on the EU Immigration Regulations with Particular Attention to the Principle of Solidarity and Fair Sharing of Responsibility Between Member States Analysis of the influence of the Treaty of Lisbon on the EU immigration regulations with particular attention to the principle of solidarity and fair sharing of responsibility between Member States indicates that the Treaty of Lisbon extensively reformed these regulations. Its premise and mechanisms should be assessed as justified. However, they give a lot of leeway for interpretation and need to be supplemented with EU secondary law. Unfortunately, states are primarily driven by their interest when applying these rules which leads to their nonproductiveness. The recent migration crisis explicitly proves this. The reason for the above can be found, among other things, in attachment to classic understanding of state sovereignty and in the lack of the definition of solidarity principles and fair sharing of responsibility between Member States. Postulated reforms do not guarantee solving this problem either.